Soldagem por fricção convencional entre a liga de alumínio 6351-T6 e o aço SAE 1020 assistida por indução eletromagnética - Sheron Stephany Tavares (2017)
Friction welding has become interesting in terms of its application. In this context, this paper aimed to evaluate the effect of preheating the conventional friction butt welding between the aluminum alloy AA 6351-T6 and low-carbon steel SAE 1020. For developing this work, an adapted and instrumented drill press was used to make dissimilar joints. The welding was done under two conditions: without preheating and with electromagnetically induced preheating to about 350°C, applied to the steel-aluminum interface. The compression stress and torque could be monitored during welding by using a load cell attached to the drill table. The welding parameters, with the exception of friction time, were kept constant for both conditions because a new variable was introduced to the process, namely the preheating temperature. The bonding interface characterisation was done using an optical microscopy (OM) and scanning electron microscopy (SEM-EDX). Vickers microhardness and traction testing were used to evaluate the welding mechanical strength. The results obtained shown that preheating application decreases the total time of the process by 50%. The SEM-EDX analysis showed that there was interdiffusion amid the main elements contained in the materials applied. For both welding conditions, the failure occurred on the bonding interface of the specimens. The temperature recorded in the steel for welds without preheating was 400°C and welds with preheating 418°C.